(untitled) (Darya Ganj, New Delhi, 2004)
Contents of material: Principles and issues of metadata. organisational metadata. Metadata channels. Automatic extraction. Hypertextual interface. Metadata usability. Metadata: Tasks and commitments
Keywords: Information organization,Library science,Metadata,Metadata,Libraries,Digital libraries; Electronic information resources